Design and implementation of cooking oil and water filtration system for domestic application - Sudiskumar D.; Ismail F.B.; Nasif M.S. (Asian Research Publishing Network, 2023)
Piping is an important system within any premise. Without a proper piping system, daily activities would be disrupted. As such kitchens are one of the premises that utilise water in large amounts. However, there are a lot of oily content in the waste water that is being flushed away in the sink of a kitchen. As a result, this oily content slowly builds up on the wall of the pipeline slowly forming greasy layer eventually causing pipe blockage. The greasy layer also attracts solid waste that is being disposed in the sink that forms large clumps within the pipeline which makes the blockage even worse. Within this study a new method was adopted in order to prevent these types of blockages. A mechanism that utilises hydro cyclone as the separator will be used to prevent the blockages from happening. The idea is to separate the oily content of the water from the waste water before it enters the exit pipeline. The concept was tested by running simulation using Computational Fluid Dynamics (CFD). The major outcome of the system was that it is capable of functioning at an efficiency of 83% with very minimal oil content at the water exit. This 83% denotes the amount of oil that is passing through the oil exit of the system. The rest of the 17% is water. These values are to be improved in future works. 2006-2016 Asian Research Publishing Network (ARPN).